Polyhydroxybutyrate for improved oil recovery: a literature review / Norrulhuda Mohd Taib, Norfarisha Achim and Zulkafli Hassan - Mohd Taib, Norrulhuda; Achim, Norfarisha; Hassan, Zulkafli (Penerbit UiTM (UiTM Press), 2016)
In this study the role of polymer flooding as one of the most efficient processes to enhance oil recovery (EOR) is discussed. Polyhydroxybutyrate (PHB) is a bio-based polymer that has potential application for use in polymer flooding. This polymer is reviewed with particular emphasis on the effect of concentration, shear rate, salinity, hardness and temperature on polymer viscosity. Initial findings showed that PHB owned higher resistant as compared to mechanical degradation and thermal stability of HPAM as well as XG.